Monotonic and cyclic flexural behaviour of square/rectangular rubberized concrete-filled steel tubes. (December 2017) - Silva, A.; Jiang, Y.; Castro, J.M.; Silvestre, N.; Monteiro, R.
Abstract: This paper focuses on the assessment of the behaviour of Concrete Filled Steel Tube (CFST) columns with square/rectangular cross-section, made with Rubberized Concrete (RuC), under flexural loading. The study aims to evaluate the differences between this type of composite members and typical CFST members made with standard concrete (StdC), namely in terms of the influence of the rubber aggregate replacement ratio on member strength, ductility, and energy dissipation capacity. The experimental campaign comprised the testing of 16 square members, 12 RuCFST and 4 StdCFST, and 4 rectangular RuCFSTs. A number of parameters were investigated, namely the cross-section slenderness (i.e., the width-to-thickness ratio of the steel tube), the aggregate replacement ratio (i.e., the percentage of sand aggregate of the concrete mixture that is substituted by rubber particles), axial load level and lateral loading type. The test results are compared with the member capacities obtained with the application of Eurocode 4. The results show a minimal influence of the type of concrete infill on the monotonic and cyclic behaviour of the members and also allow concluding that the European code is conservative in predicting the capacity of the specimens. Furthermore, the results obtained demonstrate that the cross-section slenderness has an important role on the behaviour of these members. Nonetheless, the requirements pertaining this parameter that are currently defined in Eurocodes 4 and 8 can be relaxed. Graphical abstract: Highlights: Experimental assessment of the flexural behaviour of square/rectangular rubberized CFSTs is presented Influence of concrete typology, cross-section slenderness and lateral loading regime on the flexural response of CFSTs is presented Square/rectangular CFST and RuCFST test specimens exhibited a ductile behaviour, both under monotonic and cyclic loading Test results point to a possible relaxation of the cross-section slenderness limits defined in Eurocode 4 and 8.